2013
DOI: 10.1111/soin.12018
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Loneliness and Health in Early Adulthood

Abstract: The health consequence of loneliness in the early life course is an understudied topic in the sociological literature. Using data from Waves 1–3 of the National Longitudinal Study of Adolescent Health, we examine pre‐disease pathways in the relationship between adolescent loneliness and early adult health. Our results indicate that loneliness during adolescence is associated with diagnosed depression, poorer adult self‐rated health, and metabolic risk factors related to cardiovascular disease. High depressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
108
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 72 publications
5
108
0
2
Order By: Relevance
“…BMI, systolic blood pressure, cholesterol levels, glycated haemoglobin concentration, maximum oxygen consumption). Similarly, Goosby et al [34] found that loneliness in adolescence predicted a greater risk for high cholesterol, high blood pressure and overweight/obesity in young adulthood. The effect of loneliness on these metabolic risk factors was shown to be explained in part by depression and low parental support in adolescence.…”
Section: (D) Early and Mid-adulthood (18 -49 Years)mentioning
confidence: 91%
See 4 more Smart Citations
“…BMI, systolic blood pressure, cholesterol levels, glycated haemoglobin concentration, maximum oxygen consumption). Similarly, Goosby et al [34] found that loneliness in adolescence predicted a greater risk for high cholesterol, high blood pressure and overweight/obesity in young adulthood. The effect of loneliness on these metabolic risk factors was shown to be explained in part by depression and low parental support in adolescence.…”
Section: (D) Early and Mid-adulthood (18 -49 Years)mentioning
confidence: 91%
“…poorer general health [27]; more somatic symptoms [28] ! poorer general health [32,51]; see also [28,34] ! poorer general health [33,34] !…”
Section: Loneliness and Its Health Effects Across The Lifespanmentioning
confidence: 99%
See 3 more Smart Citations